Trichodinid (Ciliophora: Peritrichida) Ectoparasites of Sand Goby (Oxyeleotris marmorata) Fry - Dana, D.; Sumawidjaja, Kusman; Hadiroseyani, Yani (Indonesian Society of Scientific Aquaculture (ISSA), 2002)
ABSTRACTTwo species of Trichodinid were identified from sand goby, (Oxyeleotris marmorata) fry of 6,1-8,0 mm long; T heterodentata and T nigra. All parasite species were scraped from the skin of fry which were reared in fertilized pond.Key Word : Sand goby, trichodinids ABSTRAKDua spesies dari genus Trichodina telah diidentifikasi dari benih ikan Betutu, (Oxyeleotris marniorata) yang berukuran 6,1-8,0 mm. Kedua spesies itu adalah T heterodentata dan T nigra. Parasit tersebut diambil dari kulit ikan betutu yang dipelihara dalam kolam yang dipupuk.Kata kunci : Ikan betutu, trichodina